2010
DOI: 10.1002/humu.21151
|View full text |Cite
|
Sign up to set email alerts
|

Detailed haplotype analysis at theTP53locus in p.R337H mutation carriers in the population of Southern Brazil: evidence for a founder effect

Abstract: Due to patterns of migration, selection, and population expansion, founder effects are common among humans. In Southern Brazil, a recurrent TP53 mutation, p.R337H, is detected in families with cancer predisposition. We have used whole locus resequencing and high-density single nucleotide polymorphism (SNP) genotyping to refine TP53 locus haplotype definitions. Haplotyping of 12 unrelated p.R337H carriers using a set of 29 tag SNPs, revealed that all subjects carried the same haplotype, and presence of the muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(149 citation statements)
references
References 28 publications
6
129
0
14
Order By: Relevance
“…Carriers of this specific TP53 mutation (R337H) have a low risk of developing cancer before the age of 30, but a lifetime cancer risk comparable to classic LFS [105,106]. Interestingly, 90-95% of all patients with adrenocortical carcinomas have the TP53-R337H mutation leading to a drastic increase of this cancer form in the southern provinces of Brazil [107].…”
Section: Li-fraumeni (Tp53) Syndrome (Lfs)mentioning
confidence: 99%
“…Carriers of this specific TP53 mutation (R337H) have a low risk of developing cancer before the age of 30, but a lifetime cancer risk comparable to classic LFS [105,106]. Interestingly, 90-95% of all patients with adrenocortical carcinomas have the TP53-R337H mutation leading to a drastic increase of this cancer form in the southern provinces of Brazil [107].…”
Section: Li-fraumeni (Tp53) Syndrome (Lfs)mentioning
confidence: 99%
“…Despite the previous alternative theories, a recent study has confirmed that the high prevalence of this mutation, around 0.3% in the population of this region, results from the occurrence of a founder effect in the Brazilian population. In Southern Brazil the incidence of childhood ACC is 10-15 higher compared with other parts of the world, being strongly associated with the p.R337H mutation [115][116][117].…”
Section: Prace Poglądowementioning
confidence: 97%
“…Pomimo wcześniejszych alternatywnych teorii, ostatnie badania potwierdzają, że wysoki współczyn-nik występowania tej mutacji u około 0,3% populacji tego regionu wynika z wystąpienia efektu założyciela w populacji Brazylii. W południowej Brazylii częstość występowania ACC u dzieci jest 10-15-krotnie wyższa niż w innych częściach świata i jest silnie związana z mutacją p.R337H [115][116][117].…”
Section: Prace Poglądoweunclassified
“…biallelic MUTYH mutation associated colon cancer) [33,38]. Further developments in high-throughput, cost-effective mutation screening methods that generally applied Sanger sequencing in a validation phase made possible considerable candidate gene sequencing and resequencing that further defined mutation frequency and associated cancer risks [39][40][41][42][43][44][45] (see Fig. 1).…”
Section: The Search For Cancer Predisposition Genesmentioning
confidence: 99%